2020
DOI: 10.35765/mjse.2020.0917.08
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages and Limitations of Translanguaging in Teaching Third of Additional Languages at the University Level

Abstract: The purpose of the paper is an analysis of the advantages and limitations of the use of translanguaging, or the mobilisation of students’ whole multilingual repertoires to facilitate understanding and learning (Lewis, Jones, Baker, 2012, p. 655), in the teaching of third or additional languages (De Angelis’s (2007) term) at the university level. The paper is based on two studies by the [name deleted to maintain the integrity of the review process], on the use of translanguaging in the teaching of Spanish [name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, this could be overcomed when teachers give enrichment activities for the students as a way to encourage and motivate them. Students who are good in a particular language or have been taught not to mix languages may regard the approach of translanguaging as unusual, and they may require encouragement to continue with the learning (Wlosowicz, 2020). From this point, it gives a solution for teachers on how to tackle the higher proficiency student in engaging them throughout the lesson.…”
Section: Somewhat Importantmentioning
confidence: 99%
“…However, this could be overcomed when teachers give enrichment activities for the students as a way to encourage and motivate them. Students who are good in a particular language or have been taught not to mix languages may regard the approach of translanguaging as unusual, and they may require encouragement to continue with the learning (Wlosowicz, 2020). From this point, it gives a solution for teachers on how to tackle the higher proficiency student in engaging them throughout the lesson.…”
Section: Somewhat Importantmentioning
confidence: 99%
“…While there are some benefits of translanguaging in teaching English in the classroom, some other opposite findings (Wlosowicz, 2020) showed that some teachers find it difficult to implement the technique as they lack experience doing it. And, students of a beginner level, find it difficult and confusing to hear the teachers change the language during the class.…”
Section: Interviewermentioning
confidence: 99%
“…Although once considered lower performers than the monolinguals [11], bilinguals are believed to be better performers in the literacy skills and at the same time in the acquisition of second or foreign language. Both teacher and students can take the most benefit of empowering the existing knowledge and language awareness to facilitate understanding and learning [12,13]. The empowerment of these knowledge and awareness was the foundation of pedagogical translanguanging.…”
mentioning
confidence: 99%